Transcendência inclusiva: do legal ao social: a invisibilidade dos excluídos e a importância da tutela processual individual dos direitos fundamentais para a consagração da dignidade da pessoa humana. - França, Alcides Pereira de (2011)
This paper proposes the inclusion of a segment of society excluded from social life to work in process through the adoption of procedural substitution inclusive, under the auspicious principles of constitutional guarantees, the establishment of development standards procedure additive to Article 6 of the CPC, Which provide the conditions to justify extraordinarily others, giving you access to the judiciary, independent of the pole that will appear on demand, ie, integrating legitimating the situation, so you can act on their own behalf in court in defense of rights of others In favor of persons deprived of minimum conditions for exercising this right, able to ensure accessibility to all who knock the doors of state-court thus considered as "patients", like the "history' habeas corpus, covering them with inafastabilidade the principle of jurisdiction, also named right of action, or principle of free access to the judiciary, or, as noted Pontes de Miranda, the principle of ubiquity of Justice. This is because the legitimacy of taxation law requires prior recognition of citizenship as the basis of a democratic state, here in Brazil, the principle of human dignity, constitutionally expressed, lives with excluded from all species produced by a model society becomes more and more impervious to living together in fellowship of men.